2014
DOI: 10.1371/journal.pone.0088409
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Classification and Differential Expression of Oleosin Genes in Tung Tree (Vernicia fordii)

Abstract: Triacylglycerols (TAG) are the major molecules of energy storage in eukaryotes. TAG are packed in subcellular structures called oil bodies or lipid droplets. Oleosins (OLE) are the major proteins in plant oil bodies. Multiple isoforms of OLE are present in plants such as tung tree (Vernicia fordii), whose seeds are rich in novel TAG with a wide range of industrial applications. The objectives of this study were to identify OLE genes, classify OLE proteins and analyze OLE gene expression in tung trees. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
3
20
0
Order By: Relevance
“…FAD2 and FADx were highly expressed in mid-late stages of developing seeds; whereas FAD3 was expressed higher in early stages of seed, also in agreement with published results [14]. All five OLE s were highly expressed in mid-late stage of developing tung seeds, similar results to what we reported previously [26]. Our expression analysis provided novel insights into the potential role of PDAT s in tung oil biosynthesis by showing that PDAT1-1 , 1-4 , and 2-2 were expressed more in mid-late stages of developing seeds but the other three PDAT genes were expressed more in the early stages of developing seeds, which were not reported previously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…FAD2 and FADx were highly expressed in mid-late stages of developing seeds; whereas FAD3 was expressed higher in early stages of seed, also in agreement with published results [14]. All five OLE s were highly expressed in mid-late stage of developing tung seeds, similar results to what we reported previously [26]. Our expression analysis provided novel insights into the potential role of PDAT s in tung oil biosynthesis by showing that PDAT1-1 , 1-4 , and 2-2 were expressed more in mid-late stages of developing seeds but the other three PDAT genes were expressed more in the early stages of developing seeds, which were not reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…OLEs are the major proteins in plant oil bodies. Genome-wide phylogenetic analysis and multiple sequence alignment demonstrated that the five tung OLE genes represented the five OLE subfamilies and all contained the “proline knot” motif (PX5SPX3P) shared among 65 OLE from 19 tree species [26]. We confirmed the five tung tree OLE genes coding for small hydrophobic proteins.…”
Section: Resultssupporting
confidence: 63%
“…Inhibition of the major oleosin gene (18 kD) expression in Arabidopsis resulted in unusually larger oil bodies, disruption of storage organelles and significant decrease in the amount of lipids (Siloto et al, 2006). On the contrary, overexpression of soybean oleosin gene (24 kD) in transgenic rice seed significantly improved the lipid content with massive smaller oil bodies (Cao et al, 2014). In our work, oleosins were identified from both Vernicia and Jatropha, each with 6 distinctive members.…”
Section: Discussionmentioning
confidence: 54%
“…They provide fatty acids for membrane biogenesis and lead to obesity if excessive amounts of fats accumulate in adipose tissues (Chapman et Walther, 2009;Somerville et al, 2000). Plant TAGs are both for human consumption and for industrial applications (Cahoon et al, 2007;Dyer et al, 2008) including biofuel production (Carvalho et al, 2008;Chen et al, 2010b;Tai and Stephanopoulos, 2013;Winichayakul et al, 2013). Many trees contain up to 50%-80% of oil in the seeds and fruits (Cao et al, 2013;Chen et al, 2008;Zeng et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%